Elaboration and validation of check list for allergens control in food services (Research, Society and Development, 2021)
Food allergy is considered a relevant issue for public health, requiring the implementation of allergen control in order to protect the consumer's health, as it compromises the quality of life and can lead to extreme reactions, such as anaphylaxis, a systemic reaction that can lead to death. The aim of this study was to prepare and validate a checklist for allergen control in food services applying the multiple case study method. The checklist was adapted from the literature review in the scope of food safety in the allergen category, comprising 33 items with 10 groups. The instrument for data collection was this checklist which document was applied in two Japanese cuisine restaurants and a cafeteria located in the Rio de Janeiro city. The main non-compliance observed were related to the dimension of commercial establishments, the lack of employees training, failures in supplier management resulting in inadequate storage, difficulty of separating areas, containers and utensils, and surfaces cleaning. It was also possible to observe that these establishments handled an excessive number of allergens and consequently expose consumers to risks. It can be concluded that the checklist elaborated constitutes a tool of easy and application and implementation of allergen management, which can stimulate the necessary adoption of an allergen control program in commercial establishments of this segment.